Suitability of Legume Cover Crop Mixtures in Central South Dakota for Late‐season Forage. Issue 1 (26th June 2015) - Hansen, Matthew J.; Owens, Vance N.; Beck, Dwayne; Sexton, Peter
Abstract : Cover crops provide many agronomic benefits and can be a useful forage resource. The objectives of this study were to determine (i) suitable forages based on yield and quality; and (ii) changes in feed value and yield of these crops through the late fall. Six legume cover crop mixtures, consisting mainly of chickling vetch ( Lathyrus sativus L.), field pea ( Pisum sativum L.), and rape ( Brassica napus L.), were planted at Dakota Lakes Research Farm after winter wheat ( Triticum aestivum L.) harvest in 2010 and 2011 and were sampled at three fall dates, approximately 1 October, 1 November, and 1 December, to determine changes in yield and quality. Due to poor emergence of rape in 2010 all the mixtures had similar yields and quality values. Emergence of rape in 2011 decreased fiber and protein concentrations of the mixtures it was in. Yields for the mixtures ranged from 933 to 4590 kg ha −1 over the two years, with yields increasing after the first harvest date both years. Crude protein concentrations ranged from 113 to 270 g kg −1 for all treatments. All mixtures showed good forage potential, with some fiber supplementation needed in 2011 due to the high amounts of rape present in some mixtures.